2019
DOI: 10.3389/fpsyg.2019.01801
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Choice and Caregiver Outcomes: A Longitudinal Study of Irish Spousal Dementia Caregivers

Abstract: Background The perception of choice in becoming a caregiver may impact on caregiver psychological and physical health. We determined the proportion of spousal dementia caregivers who felt they had a choice, and examined whether lack of choice in taking up the caregiving role and the perceived degree of choice in caregiving predicted caregiver health and wellbeing and care-recipient placement in long-term care at 1-year follow-up. Methods We performed secondary analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…They provide the care that the state would otherwise have to fund at significant cost to the taxpayer. Although providing care voluntarily, one Irish study of spousal carers indicated many carers feel they have no other choice but to provide care (Pertl et al, 2019). Emotional ties, lack of care alternatives, economic factors, societal expectations and familial responsibility can be contributors to this perceived lack of choice (Al-Janabi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They provide the care that the state would otherwise have to fund at significant cost to the taxpayer. Although providing care voluntarily, one Irish study of spousal carers indicated many carers feel they have no other choice but to provide care (Pertl et al, 2019). Emotional ties, lack of care alternatives, economic factors, societal expectations and familial responsibility can be contributors to this perceived lack of choice (Al-Janabi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the first point, the “birth” of a caregiver offers the earliest opportunity to identify people in need of support. Indeed, as past research has documented, becoming a caregiver is a turning point in one’s life trajectory [ 22 ], and for relatives, it seems to be less a matter of choice than a matter of responsibility and reciprocity [ 23 , 24 ]. Considering that feelings of control in caregiving relate to caregivers’ wellbeing and that the decision to become a caregiver is an indicator of control [ 25 ], caregivers who choose to take on caregiving might experience higher levels of control than caregivers who “slipped into it”.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, research has largely focused on the stress and burden characterizing caregivers' daily-life (Lazarus and Folkman, 1984;Pearlin et al, 1990;Zarit and Femia, 2008;Giovannetti et al, 2013;Tan et al, 2019) along with the personal losses resulting from their newfound responsibilities (loss of autonomy, relinquishing of anticipated future plans, etc.) (Pertl et al, 2019). Changes to their belief system regarding the world and the self were also noted ("assumptive world") (Janoff-Bulman, 1992;Parkes, 2001;Harris, 2011).…”
Section: From Stress and Burden To Grief And Mourning In Non-death Bereavementsmentioning
confidence: 99%